The Environment of Pedagogic Creativity and its Redusing Factors - I. S. Ogonovskaya (Russian State Vocational Pedagogical University, 2015)
The paper is devoted to the issue of pedagogic creativity, its development and existence within the real environment of educational estab- lishments limited by their objective and subjective factors. The research is aimed at investigating the conditions affecting teacher's creativity, the latter being viewed as an integral characteristic including intellectual and emotional flexibility, imagination, intuition, capability of overcoming the stereotypes, working in nonstandard situations and aspiring for new ways. The research is based on the traditional pedagogic methods of observa- tion and testing, and collective phenomena investigation methods of ques- tionnaires, socio-metrics, etc. The main conclusion concerning the environ- ment of pedagogic creativity reveals its limited nature. In author's opinion, the systematic outside pressing, freedom restrictions, work depersonalization, alienation of the most talented teachers can adversely affect the creative ap- proach to teacher's professional activity and quality motivation. The research findings might be of interest to heads of educational es- tablishments and teachers.